2013
DOI: 10.7314/apjcp.2013.14.1.557
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Profiling of Intrahepatic Cholangiocarcinoma

Abstract: Intrahepatic cholangiocarcinoma (ICC) is ranked as one of the top five causes of cancer-related deaths. ICC in Thai patients is associated with infection with the liver fluke, Opisthorchis viverrini, but the molecular basis for development remains unclear. The present study employed a microarray approach to compare gene expression profiles of ICCs and normal liver tissues from the same patients residing in Northeast Thailand, a region with a high prevalence of liver fluke infection. In ICC samples, 2,821 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 41 publications
2
28
2
1
Order By: Relevance
“…MACC1 mRNA expression was approximately 10 times higher in ICC and Klatskin tumors than in peritumorous normal liver tissue. Gene expression profiling in ICCs also showed elevated MACC1 expression levels . Whereas MACC1 expression in the Klatskin tumor cohort did not differ between UICC tumor stages, we found significantly higher MACC1 expression values in patients with a tumor size of pT3 and pT4, compared to pT1 and pT2.…”
Section: Discussionsupporting
confidence: 91%
“…MACC1 mRNA expression was approximately 10 times higher in ICC and Klatskin tumors than in peritumorous normal liver tissue. Gene expression profiling in ICCs also showed elevated MACC1 expression levels . Whereas MACC1 expression in the Klatskin tumor cohort did not differ between UICC tumor stages, we found significantly higher MACC1 expression values in patients with a tumor size of pT3 and pT4, compared to pT1 and pT2.…”
Section: Discussionsupporting
confidence: 91%
“…Various ITIH family members are down-regulated in a variety of human malignant tumors [25-27]. Paris et al .…”
Section: Discussionmentioning
confidence: 99%
“…This provided exon-level expression profiles, which might be useful for early diagnosis of CCA. 17 Shigehara et al demonstrated that some miRNAs (miR-9, miR-302c, miR199a-3p and miR-222) in human bile were more highly expressed in biliary tract cancer than in benign conditions, so miR-9 might be helpful in the diagnosis and clinical management of biliary tract cancer. 18 Markers for the precise prediction of the prognosis of CCA have been difficult to identify.…”
Section: Diagnosismentioning
confidence: 99%